Can web crawlers revolutionize ecological monitoring?. Issue 2 (19th March 2009) - Galaz, Victor; Crona, Beatrice; Daw, Tim; Bodin, Örjan; Nyström, Magnus; Olsson, Per
Abstract : Despite recent advances, ecosystem service monitoring is limited by insufficient data, the complexity of social–ecological systems, and poor integration of information that tracks changes in ecosystems and economic activities. However, new information and communication technologies are revolutionizing the generation of, and access to, such data. Can researchers who are interested in ecological monitoring tap into these increased flows of information by "mining" the internet to detect "early‐warning" signs that may signal abrupt ecological changes? Here, we explore the possibility of using web crawlers and internet‐based information to complement conventional ecological monitoring, with a special emphasis on the prospects for avoiding "late warnings"– that is, when ecosystems have already shifted to less desirable states. Using examples from coral reef ecosystems, we explore the untapped potential, as well as the limitations, of relying on web‐based information to monitor ecosystem services and forewarn us of negative ecological shifts.